Domestic violence behind closed doors - Andrews, Cindy; Bonfleur, Bette; Chapman, Robin; Ivanhoe Communications; Films for the Humanities (Firm) (Princeton, N. J. : Films for the Humanities & Sciences, 2004)
This program shows how people can and have said'Enough!': women, men, and children who offer proof that domestic violence can be stopped, that healing is possible if thereis someone to help. The program also shows the social and legal sevices that make the difference
Narrator, Robin Chapman
Keywords: Abuse women -- United States; Abuse wives -- United States; Family violence -- United States; Spouse abuse; Violence